CAPACITY BUILDING AND EMPLOYEE PERFORMANCE IN ANAMBRA STATE CIVIL SERVICE COMMISSION (2014-2024) (Journal of the Management Sciences, 2025)
This study examined the effect of capacity building on employee performance in Anambra State Civil Service Commission (2014-2024). The specific objectives were to: Determine the effect of employee orientation, training and job rotation and transfer on employee performance in Anambra State Civil Service Commission, Three research questions and hypotheses were formulated in line with the objectives and the study anchored on human capital theory. Cross-sectional survey was used and data were drawn mainly from the primary source through the instrumentality of structured questionnaire augmented with structured interview and focal group discussion. A multi-stage purposive sampling technique was used to select 211 respondents of which 205 valid questionnaires of respondents were used for the final analysis in the selected nine ministries. Both descriptive and inferential statistical tools were used for data analysis while multiple linear regressions were used for hypotheses testing. Findings revealed that job orientation has a significant positive effect on employee performance, training was also found to have a highly significant positive effect while employee job rotation and transfer significantly influenced performance. Thus, the study recommends that public organizations should continually organize employee orientation and training programmes as this will help employees to be well acquainted with their job roles and environment among others.
Keywords: Capacity building; Employee orientation; Training; Job rotation and transfer; Employee performance; Anambra State Civil Service Commission